Odpowiedzi

Najlepsza Odpowiedź!
  • Evil
  • Początkujący
2009-10-04T13:17:47+02:00
2009-10-04T13:24:57+02:00
A) {0,4x+y=6
{x+0,75y=8 => x=8-0,75y

0,4*(8-0,75y)+y=6
3,2-0,3y+y=6
0,7y=2,8
y=4



b) {2x=1-3y
{½ x =2-y /*-4 => -2x=-8+4y dodajemy dwie strony
0=-7+y czyli y=7


2009-10-04T13:36:15+02:00
A) 0,4x+y = 6
z+0,75y=8

y=6-0,4x
x=8-0,75(6-0,4x)

y=6-0,4x
0,2x = 3,5 /:0,2

y=6-0,4*17,5
x=17,5

y=6-7
x=17,5

y=-1
x=17,5

b) 2x=1-3y
1/2x=2-y /*2

2x=1-3y
x=4-2y

2(4-2y)=1-3y
x=4-2y

8-4y = 1-3y
x=4-2y

-y=-7 /*(-1)
x=4-2y

y=7
x=4-2*7

y=7
x=10

c) x-y-3=0
2x+3y - 11 = 0

x=y+3
2(y+3)+3y-11=0

x=y+3
2y+6+3y-11=0

x=y+3
5y=5 /:5

x=y+3
y=1

x=4
y=1

d) -3(x+2)+2(x+y)=2
2(y+2)+3(x-y)=2x-1

-3x-6+2x + 2y = 2
2y+y+3x-3y=2x-1

-x+2y-6=2
-y+4+3x=2x-1

-x=8-2y /*-1)
-y+4+6y-24 = 4y-17

x=2y-8
-y+6y-20=4y-17

x=2y-8
-y=3 /*(-1)

x=2y-8
y=-3

x=2(-3) -8
y=-3

x=-9-8
y=-3

x=-1
y=-3